Political Consciousness and Participation in the Defense of LGBTQ+ Rights at Work - Mongin Boasquevisque, Leôni; Prezotti Palassi, Márcia; Rodrigues Leite da Silva, Alfredo (Organizações & Sociedade, 2024)
This article aims to understand the psychopolitical aspects of the participation of call center workers, trade unionists, and leaderships within collectives in collective actions to defend LGBTQ+ rights at work. The research adopts the conceptual framework of political consciousness developed in the field of political psychology by Sandoval and Silva (2016). Data were produced qualitatively in two stages: interaction with research participants to present the topic and determine their willingness to address its most sensitive aspects; provision of different online questionnaires with qualitative focus for research participants: 14 call center workers, 2 trade unionists, and 6 LGBTQ+ leaderships within collectives. Content analysis of the statements showed heterogenous political consciousness among research participants, in differences involving their political engagement or lack thereof. By discussing these aspects, we filled the gap of works in the field of organizational studies, human resource management, and labor relations, which use theoretical contributions from the psychopolitical approach to address the (de)mobilization of different subjects in the defense of LGBTQ+ rights at work in these fields of knowledge. For the workers, trade unionists, leaderships within collectives and society, these theoretical contributions enabled observing that the coordination between unions and collectives tends to promote the raising of a critical political consciousness, fostering joint actions in the fight for LGBTQ+ rights at work